ANALISIS PROSES PEMBUATAN KEBIJAKAN PUBLIK (STUDI KEPUSTAKAAN: UU TINDAK PIDANA KEKERASAN SEKSUAL (TPKS) DI INDONESIA) - Octavia, Andi Arba; Winarto, Andri (Jurnal Administrative Reform, 2025)
This research article aims to describe and analyze the process of making public policy in Indonesia on the TPKS Law (Criminal Acts of Sexual Violence). The research employs a descriptive qualitative approach with a library research method, in which data were collected from various relevant literature sources such as books, academic journals, legislative documents, and previous research reports. The data were analyzed using a thematic analysis approach based on Creswell’s analytical steps, including data collection, filtering, categorization, description, and interpretation. The theoretical framework used is Nugroho’s public policy process model, which consists of six main stages: problem identification, agenda setting, policy formulation, policy legitimation, policy implementation, and policy evaluation. The results indicate that the formulation process of the UU TPKS generally aligns with the theoretical stages, although several obstacles were identified, such as political deadlock, limited understanding among implementers, and lack of public participation. This research contributes theoretically to public policy studies and opens avenues for future research, particularly in examining policy implementation at the local level and evaluating the effectiveness of the UU TPKS post-enactment.